1988
DOI: 10.1056/nejm198809013190905
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration and Repair of Myelinated Fibers in Sural-Nerve Biopsy Specimens from Patients with Diabetic Neuropathy Treated with Sorbinil

Abstract: There is reason to believe that diabetic neuropathy may be related to the accumulation of sorbitol in nerve tissue through an aldose reductase pathway from glucose. Short-term treatment with aldose reductase inhibitors improves nerve conduction in subjects with diabetes, but the effects of long-term treatment on the neuropathologic changes of diabetic neuropathy are unknown. To determine whether more prolonged aldose reductase inhibition reverses the underlying lesions that accompany symptomatic diabetic perip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
146
0
1

Year Published

1990
1990
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 298 publications
(153 citation statements)
references
References 51 publications
6
146
0
1
Order By: Relevance
“…With the rationale that excessive flux of glucose via this enzyme contributes to diabetic injury, several AKR1B-specific inhibitors have been synthesized. Initial small-scale clinical trials showed that inhibition of this enzyme could ameliorate symptomatic somatic and autonomic neuropathies (Jaspan et al, 1983), improve joint mobility (Eaton et al, 1985) and could prevent or delay fiber degeneration in neuropathy (Dyck et al, 1988) and partially correct nerve conduction defects in diabetics (Sima et al, 1988). Later, large-scale clinical trials, however, failed to demonstrate clear benefit and were marred with non-specific sensitivity reactions or off-target effects.…”
Section: Iii) Inhibitorsmentioning
confidence: 99%
“…With the rationale that excessive flux of glucose via this enzyme contributes to diabetic injury, several AKR1B-specific inhibitors have been synthesized. Initial small-scale clinical trials showed that inhibition of this enzyme could ameliorate symptomatic somatic and autonomic neuropathies (Jaspan et al, 1983), improve joint mobility (Eaton et al, 1985) and could prevent or delay fiber degeneration in neuropathy (Dyck et al, 1988) and partially correct nerve conduction defects in diabetics (Sima et al, 1988). Later, large-scale clinical trials, however, failed to demonstrate clear benefit and were marred with non-specific sensitivity reactions or off-target effects.…”
Section: Iii) Inhibitorsmentioning
confidence: 99%
“…A double-blind study in patients with diabetic neuropathy by Sima et al [115] gave exciting evidence of the efficacy of sorbinil, an aldose reductase inhibitor, against morphological signs of degeneration accompanied by a decrease in the nerve sorbitol level and an increase in the nerve conduction velocity. A similar observation was reported by Greene et al [116] using another aldose reductase inhibitor, FK-366.…”
Section: Inhibition Of Increased Polyol Pathwaymentioning
confidence: 99%
“…The nerve dysfunction as a consequence of diabetes is debilitating and can lead to lifethreatening autonomic neuropathy, cardiac diseases, and CNS atrophy (3,4). Dying back of distal peripheral nerve fibers because of glucose toxicity and the ensuing spinal sensitization are thought to be the underlying causes of pain (5)(6)(7)(8)(9). Although hyperglycemia is the initiating cause for diabetic neuropathy, aggressive glycemic control is effective in impeding the progression of neuronal loss and pain, but not in reversing neuropathy (10).…”
mentioning
confidence: 99%